User Perceptions of Sustainability Reporting - Baker, Pamela; Baker, J. Keith (Archives of Business Research, 2019)
Over the past two decades, accounting firms and corporate stakeholders began measuring and reporting social and environmental performance along with financial reporting measures in the form of a sustainability report. The number of Standard & Poor’s 500 Index (S&P 500®) firms issuing sustainability reports grew from 20% in 2011 to 81% in 2015 (Coppola, 2016) and continued to do so through 2018 (Aquila, 2018). Such reporting suggests that activists, environmentalists, and internal users find reports to be beneficial in enhancing the company’s ability to achieve long-run goals. This paper reports the opinions of senior executives about the usefulness of sustainability reports. Results indicate that executives read and use these reports as part of the complete analysis of their own and other firms, and they do not believe that additional environmental or sustainability disclosures are necessary.